Gamification-based e-learning strategies for computer programming education - Queiros, Ricardo Alexandre Peixoto de 1975-; Pinto, Mario Teixeira 1967- (Advances in game-based learning (AGBL) Book Series, 2016)
This book evaluates the different approaches and issues faced in integrating games into computer education settings, featuring emergent trends on the application of gaming to pedagogical strategies and technological tactics, as well as new methodologies and approaches being utilized in computer programming courses"--cProvided by publisher